2020
DOI: 10.35848/1347-4065/ab82a8
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance of CaF2/Si double barrier resonant tunneling diodes fabricated using plasma etching mesa isolation process

Abstract: We demonstrated the negative differential resistance (NDR) characteristics in CaF 2 /Si double barrier resonant tunneling diodes (DBRTDs) which have mesa structure isolated by the plasma etching process using CF 4 /O 2 plasma. Clear NDR characteristics with a peak to valley current ratio of 79 and a current density of 1-10 kA cm −2 was obtained from a CaF 2 /Si DBRTD mesa-isolated using CF 4 /O 2 plasma etching at room temperature. Furthermore, any degradation of performance of the DBRTD caused by dry etching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…MBE was conducted to grow crystals. [31][32][33][34] Since it has been reported that the crystal growth of Si/CaF 2 thin films at around 80 °C suppresses the island growth of CaF 2 and improves planarity, crystal growth at around 80 °C was carried out for the i-Si and CaF 2 multilayer structure in this study. For CaF 2 deposition, ionization cluster beam deposition was carried out to improve the crystallity.…”
Section: Fabricationmentioning
confidence: 99%
“…MBE was conducted to grow crystals. [31][32][33][34] Since it has been reported that the crystal growth of Si/CaF 2 thin films at around 80 °C suppresses the island growth of CaF 2 and improves planarity, crystal growth at around 80 °C was carried out for the i-Si and CaF 2 multilayer structure in this study. For CaF 2 deposition, ionization cluster beam deposition was carried out to improve the crystallity.…”
Section: Fabricationmentioning
confidence: 99%